Pre-Operative MRI in evaluation of Perianal fistulas - Sawant, Milind; Singh, Giriraj; S, Harish; Roy, Kaushik (Asian Journal of Medical Sciences, 2021)
Background: Perianal fistula is a common and often an extremely distressing disorder. MRI is a preferred modality for the preoperative assessment of perianal fistulas. Aims and Objective: To evaluate the accuracy and predictive values of pre-operative MRI in diagnosing severity of perianal fistulas and the conditions associated with it like internal anal opening, secondary tract, abscess and supralevator extension. Materials and Methods: In this study, 44 patients with clinically suspected perianal fistulas underwent MRI for the evaluation of severity and presence of the associated conditions. St James’s University Hospital Classification was used to grade the perianal fistula. Pre-operative MRI grading was compared with the surgical findings in the 26 operated patients. Results: Out of 44 clinically suspected perianal fistulas, 41 (93%) were diagnosed as perianal fistulas by MRI. The most common type was grade 1 seen in 12(27.3%) patients followed by grade 4 fistula seen in 10(22.7%) patients. All 26 patients evaluated by surgical findings for severity of perianal fistulas were found to be graded in identical grades by pre-operative MRI. MRI was 100% sensitive in picking up all five grades. Conclusion: MRI helps in the accurate delineation of fistulous tract, identification of secondary tract and abscess.